THE SPECIFIC CHARACTER OF EVOLUTION OF FLUID-SILICATE-METALLIC IMMISCIBILITY OF MELTS - Marakushev A.A.; Rimkevich V.S.; Dem'yanova L.P. (My University, 2007)
Immiscibility in natural melts (magmas), which is expressed either in layering of intrusions or in formation of a droplike texture, develops under the influence of fluids that considerably decrease the crystallization temperature. Rhythmic magmatic layering is provided by deviation from equilibrium during fast cooling, when the melt layers have no time to change their composition, enter to the field of immiscibility, and are subjected to further immiscibility.